Quaternary benthic Foraminifera in the Tu Chinh - Vung May marine areas (continental shelf of Vietnam) and island, coral reef regions of the Truong Sa archipelago, Vietnam and their significance - Ngoc, Nguyen; Luan, Bui Thi; Nhung, Nguyen Thi Hong (Vietnam Journal of Marine Science and Technology, 2019)
The results of identifying and studying micropaleontological samples from the Quaternary sediments in the Tu Chinh - Vung May marine areas (1) and some coral reef islands of Truong Sa archipelago (2) have found more than 300 species of Benthic foraminifera, in which 291 species have been studied and described in detail, belonging to 112 genera, 43 families, 5 orders and 3 classes of the phylum Foraminifera. Among them, there are 19 new species, 3 new subspecies and 3 new genera. In the first region there are 195 species and the second one - 121 species (including 25 common species for both regions). They have important significations in the stratigraphic-biostratigraphic, ecological, paleogeographic studies, in sedimentary lithology... Regarding stratigraphy, the characteristic of Pleistocene is the first emergence of four genera: Baculogypsina, Cymbaloporetta, Parasorites, and Schlumbergerella; for Holocene - the appearance of the following genera: Ammomassilina, Baulogypsinoides, Cymbaloporella, Falsotextularia, Fijiella, Flintina, Gyroidina, Lugdunum, Neoconorbina, Planoperculina, Ptychomiliolata, Pseudoflintina, Pseudomassilina, Sahulia, Schlumbergerina, Septotextularia, Siphoniferoides, Tawitawia and Truongsaia. These fossils are the basis for dating sediment age, Quaternary stratigraphic division and correlation. In terms of paleoecology, benthic Foraminifera in the region (1) characterize the shallow offshore environment of the continental shelf, where there are the high and stable salinity, and the relatively strong environmental dynamics; in some places there are coral reef Foraminifera populations. In the region (2), they characterize the coral reef ecosystem of shallow and warm sea areas in the belt of tropical-subtropical climate of the Earth, where the salinity is high and stable, the transparency of water is high, and the environmental dynamics is relatively strong to strong... In addition, the paper also mentioned some other issues such as paleogeography (sea-level fluctuation), value of creating sediments of Foraminifera, environmental monitoring (for modern Foraminifera)